Spatio-temporal relays control layer identity of direction-selective neuron subtypes in Drosophila - Holger Apitz (Nature Portfolio, 2018)
Direction-selective T4/T5 neurons show layer-specific projections in the fly visual circuit. Examining the mechanisms behind their development, the authors found that a relay of Wnt and Bmp signaling across neuroepithelial domains and transcription factor interactions specify T4/T5 subtype identity.